Disputes and issues arising from unlawful occupation of state land in Malaysia - Syed Abdul Kader, Sharifah Zubaidah (2012)
The National Land Code 1965 declares in section 48 that there shall be no adverse possession in respect of state land and under section 425, those who are in unlawful possession of state land commit a statutory offence liable to a fine not exceeding RM10,000 and/or imprisonment for one year or both. This presentation discusses concepts relating to unlawful occupation of land, identifies the types of disputes and issues relating to the matter and explores the position under the National Land Code and differentiates the position under Malay customary tenure. Judicial approaches to unlawful occupation of state land are then discussed with reference to decided court cases on the matter. The presentation then looks at the issues of enforcement and concludes with an explanation of the human rights dimension.